Identification of BAG2 and Cathepsin D as Plasma Biomarkers for Parkinson's Disease. Issue 2 (22nd November 2020) - Kang, Juhee; Kim, Jae Whan; Heo, Hansol; Lee, Jihyun; Park, Kwan Yong; Yoon, Jung Han; Chang, Jaerak
Abstract : The current diagnosis of Parkinson's disease (PD) mostly relies on clinical rating scales related to motor dysfunction. Given that clinical symptoms of PD appear after significant neuronal cell death in the brain, it is required to identify accessible, objective, and quantifiable biomarkers for early diagnosis of PD. In this study, a total of 20 patients with idiopathic PD and 20 age‐matched patients with essential tremor according to the UK Brain Bank Criteria were consecutively enrolled to identify peripheral blood biomarkers for PD. Clinical data were obtained by clinical survey and assessment. Using albumin‐depleted and immunoglobulin G‐depleted plasma samples, we performed immunoblot analysis of seven autophagy‐related proteins and compared the levels of proteins to those of the control group. We also analyzed the correlation between the levels of candidate proteins and clinical characteristics. Finally, we validated our biomarker models using receiver operating characteristic curve analysis. We found that the levels of BCL2‐associated athanogene 2 (BAG2) and cathepsin D were significantly decreased in plasma of patients with PD ( P  = 0.009 and P  = 0.0077, respectively). The level of BAG2 in patients with PD was significantly correlated with Cross‐Culture Smell Identification Test score, which indicates olfactory dysfunction. We found that our biomarker model distinguishes PD with 87.5% diagnostic accuracy (area under the curve (AUC) = 0.875, P  < 0.0001). Our result suggests BAG2 and cathepsin D as candidates for early‐diagnosis plasma biomarkers for PD. We provide the possibility of plasma biomarkers related to the autophagy pathway, by which decreased levels of BAG2 and cathepsin D might lead to dysfunction of autophagy.